Traffic weigh-in-motion (WIM) measurements and validation of the Texas perpetual pavement structural design concept (2011)
Over the past few years, the State of Texas has used perpetual pavement (PP) structures on its heavily trafficked highways, where the expected 20-year truck-traffic estimate of 80 kN ESALs (equivalent single axle loads) is in excess of 30 million. As a means to validate the Texas PP structural design concept and to make optimal future truck-traffic design recommendations, traffic Weigh-In-Motion (WIM) measurements were conducted and analyzed for two PP projects. The findings indicated that the initial 80 kN ESAL traffic design estimates for PP were comparable to the projections based on the actual measured WIM traffic data. However, underestimation of the hot mix asphalt layer dynamic moduli resulted in conservative designs for the PP structures. In addition, based on the successful use of the automated WIM data stations for traffic data collection, the paper highlights possible applications and advantages (as compared to conventional manual collection of traffic data) of using detailed WIM traffic data information for future analyses of both highway operation and pavement structural design.